Retiring from the family business in Kumasi: an exploratory sequential study - Oteng, Samuel Ampadu (KNUST, 2025)
A Thesis submitted to the Department of Sociology and Social Work, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of Master of Philosophy in Sociology